Analysis Of Students Learning Style In English Classroom - Annisah; Waliyudin (JURNAL PENDIDIKAN BAHASA, 2019)
The purposes of this research is to analysis the students learning styles in English classroom of the fourth semester students in Education English Program Study STKIP Taman Siswa Bima in Academic years 2018/2019. This research was descriptive. The subject of this research was the fourth semester students in Pronunciation class. To collect the data the researcher used questionnaire, observation sheet, and interview questions. The result of this research was found there are 8 types of learning style used by the students in learning English. The dominant learning style used by the students were global learning style, reflective, active, Intuitive, Verbal, Sensing, Visual, and sequential learning style.